The effect of oral-like environment on dental implants' fatigue performance - Shemtov-Yona, Keren; Rittel, Daniel; Levin, Liran; Machtei, Eli E. (Clinical oral implants research, 2014)
Aim and Objectives The aim of this study was to evaluate the influence of fluid environment mimicking intra‐oral conditions on fatigue performance of standard diameter, 3.75‐mm implants. Dental implants placed intra‐orally are repeatedly submitted to mastication loads in the oral environment, which differ substantially from room‐air standard laboratory conditions. Several studies that examined fracture surfaces of intra‐orally fractured dental implants have identified corrosion fatigue as the main failure mechanism. Yet, fatigue performance of dental implants has been essentially studied in room air, based on the premise that the implant material is relatively resistant to corrosion in the intra‐oral environment. Material and methods Thirty‐two 3.75‐mm titanium alloy implants were tested under cyclic compressive loading. The tests were performed in artificial saliva substitute containing 250 ppm of fluoride. The loading machine stopped running when the implant structure collapsed or when it completed 5 × 106 cycles without apparent failure. The load vs. number of cycles was plotted as curve for biomechanical fatigue analysis (S–N curve). The S–N curve plotted for the artificial saliva test was compared to the curve obtained previously for the same implants tested in a room‐air environment. Failure analysis was performed using scanning electron microscopy (SEM). Results A comparison of the S–N curves obtained in artificial saliva and in room air showed a considerable difference. The S–N curve obtained in the artificial saliva environment showed a finite life region between 535N and 800N. The transition region was found below 465N, with a probability of survival of 50%, while in room air, the transition region was between 810N and 620N and an infinite life region below 620N was identified. Conclusions The results of this study show that environmental conditions adversely affect implants' fatigue performance. This fact should be taken into account when evaluating the mechanical properties of dental implants.